Methodological characteristics of the academic competition for general practitioners, family doctors and internists as a type of informal education - S. Yu. Astanina; S. A. Berns; S. R. Gilyarevsky; V. V. Gorban; I. V. Druk; O. N. Dzhioeva; V. V. Kashtalap; A. I. Chesnikova; E. V. Chmykhova; N. L. Shaporova; R. N. Shepel; I. S. Yavelov; et al. (Кардиоваскулярная терапия и профилактика, 2024)
The article analyzes the results of the All-Russian competition for general practitioners, family doctors and internists held over five years by the National Medical Research Center for Therapy and Preventive Medicine with the support of the Russian Society for the Prevention of Non communicable Diseases.Aim. To determine the methodological characteristics of managing the academic competition as a type of informal education.Material and methods. To conduct the competition, practice-oriented tasks corresponding to professional tasks of a general practitioner were developed. In addition, we developed an original questionnaire to assess the impact of participation in the academic competition on the professional development. Family doctors and general practitioners with 1-10 years of experience, as well as internists, were included.Results. The methodological characteristics of the academic competition management as a type of informal education were determined: practice-oriented goals aimed at improving the knowledge, skills and abilities, competencies of the participants; the content of tasks based on the theory-practice relationship; compliance of tasks and real situations in the practice of a general practitioner; a systematic approach to competition management. Conclusion. The effectiveness of the academic competition as a type of informal education contributes to the professional development of participants, promotes the development of long-term attitudes towards improving professional knowledge, skills, abilities and competencies necessary for solving professional problems.